2014
DOI: 10.3389/fnbeh.2014.00335
|View full text |Cite
|
Sign up to set email alerts
|

Visual motion-sensitive neurons in the bumblebee brain convey information about landmarks during a navigational task

Abstract: Bees use visual memories to find the spatial location of previously learnt food sites. Characteristic learning flights help acquiring these memories at newly discovered foraging locations where landmarks—salient objects in the vicinity of the goal location—can play an important role in guiding the animal's homing behavior. Although behavioral experiments have shown that bees can use a variety of visual cues to distinguish objects as landmarks, the question of how landmark features are encoded by the visual sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 78 publications
0
18
0
Order By: Relevance
“…Encoding both fast and slow motion places extensive demands on the neuronal networks underlying self-motion detection. Neurons that respond robustly to patterns of wide-field motion have been studied in several insect groups, including Dipteran flies (Hausen, 1982;Hausen and Egelhaaf, 1989), moths (Wicklein and Varju, 1999;Theobald et al, 2010;Stöckl et al, 2016), and bees (DeVoe et al, 1982;Ibbotson, 1991;Mertes et al, 2014). Typified by lobula plate tangential cells (LPTCs) of Dipteran flies, these neurons take input from local elementary motion detection (EMD) elements located in the medulla (Borst et al, 2010) and use local correlation of spatially separated inputs with asymmetric delay mechanisms, consistent with influential computational motion models (Hassenstein and Reichardt, 1956; Barlow and Levick, 1965;Gruntman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Encoding both fast and slow motion places extensive demands on the neuronal networks underlying self-motion detection. Neurons that respond robustly to patterns of wide-field motion have been studied in several insect groups, including Dipteran flies (Hausen, 1982;Hausen and Egelhaaf, 1989), moths (Wicklein and Varju, 1999;Theobald et al, 2010;Stöckl et al, 2016), and bees (DeVoe et al, 1982;Ibbotson, 1991;Mertes et al, 2014). Typified by lobula plate tangential cells (LPTCs) of Dipteran flies, these neurons take input from local elementary motion detection (EMD) elements located in the medulla (Borst et al, 2010) and use local correlation of spatially separated inputs with asymmetric delay mechanisms, consistent with influential computational motion models (Hassenstein and Reichardt, 1956; Barlow and Levick, 1965;Gruntman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One important reason for using bumblebees as a model animal is the possibility to house them indoors, which allows experiments throughout the year [ 29 ]. Furthermore, bumblebees are more robust in comparison with honeybees, which makes them suitable for several neurobiological approaches like calcium imaging [ 30 ] or single cell intracellular recording [ 31 34 ]. Additionally, bumblebees show very similar learning abilities like honeybees, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Note that step-like, i.e., saccadic direction changes are more pronounced for the head than for the body. Bottom diagram: Angular yaw velocity of body (black line) and head (red line) of the same flight (Boeddeker et al, submitted; Data from Mertes et al, 2014 ). (B) Translational and rotational prototypical movements of honeybees during local landmark navigation.…”
Section: Enhancing the Overall Power Of Insect Brains: Reducing Compumentioning
confidence: 99%
“…Recently, it could even been shown that the intersaccadic responses of bee LWCs to visual stimuli as experienced during navigation flights in the vicinity of a goal strongly depend on the spatial layout of the environment. The spatial landmark constellation that guides the bees to their goal leads to a characteristic time-dependent response profile in LWCs during the intersaccadic intervals of navigation flights (Mertes et al, 2014 ).…”
Section: Exploitation Of Environmental Information From Motion Detectmentioning
confidence: 99%